Small cell transformation in EGFR-mutated non-small cell lung cancer: DLL3 expression and efficacy of immune checkpoint inhibitors or tyrosine kinase inhibitors combined with chemotherapy - Saalfeld, Felix Carl; Möller, Johanna; Christopoulos, Petros; Wenzel, Carina; Rasokat, Anna; Wang, Xuejun Alice; Vathiotis, Ioannis; König, David; Illini, Oliver; Grohé, Christian; Wiesweg, Marcel; Wesseler, Claas; et al. (European Journal of Cancer, 2024)
Introduction: Small cell transformation (SCT) is a typical mechanism of adaptive resistance to third generation epidermal growth factor receptor inhibitors (EGFRi) which have become the standard of care for EGFR-driven non-small cell lung cancer (EGFR+ NSCLC). Little is known about the optimal management of SCT patients. This study aimed to compare outcomes under platinum/etoposide chemotherapy alone (chemo) or in combination with EGFR inhibitors (EGFRi+chemo) or immune checkpoint inhibitors (ICI+chemo). In addition, DLL3 expression was explored as potential novel therapeutic target. Methods: We conducted a retrospective study on patients with EGFR+ NSCLC and SCT treated at 19 centers in Europe and the United States. A total of 47 patients were included of whom 17 received chemo, 20 ICI+chemo, and 10 EGFRi+chemo. We analyzed DLL3 expression by immunohistochemistry. Results: In the entire cohort, median overall survival (OS) from start of first SCT therapy was 11 months (95 % confidence interval [95 %CI] 9.1–12.9) and median progression-free survival (PFS) was 5 months (95 %CI 4.2–5.8). Median PFS was similar in all three groups (chemo and ICI+chemo 4 months, EGFRi+chemo 6 months), and 12-months PFS was 12 % (95 %CI 2 %−31 %), 13 % (95 %CI 0 %−43 %), and 0 % for ICI+chemo, EGFRi+chemo, and chemo, respectively. Median OS in the ICI+chemo group was 13 months (95 %CI 5.5–20.5) compared to 10 months (95 %CI 7.6–12.4) with chemo and EGFRi+chemo (95 %CI 8.1–11.9), respectively. Before and after SCT, 0 % and 93 % of tumors were DLL3-positive. Conclusions: Our results suggest that ICI+chemo and DLL3-targeting agents are worth further exploration in EGFR+ NSCLC undergoing SCT. Presented elsewhere: Part of this work has been presented at ESMO annual meeting in Madrid, Spain in October 2023 (Poster 1336 P).
CRIS-Team Scopus Importer:2024-10-25
Keywords: DLL3; EGFR mutation; Immune checkpoint inhibitor; Non-small cell lung cancer; Small cell transformation